(untitled) (Comprehensive Journal of Science, 2026)
The conflict that occurred between 35 AH and 40 AH is considered one of the most significant events in early Islamic history. It began with the assassination of Uthman ibn Affan in 35 AH, which led to major political and social unrest within the Islamic state. Following this event, Ali ibn Abi Talib assumed the caliphate, while opposition groups demanded justice for the killers of Uthman. The conflict manifested in major battles such as the Battle of the Camel and the Battle of Siffin, involving several prominent companions of the Prophet. These events also resulted in the emergence of new political and religious groups, most notably the Kharijites. From the perspective of the philosophy of history, this period represents a turning point in the development of the Islamic political system, marking the transition from a phase of unity and cohesion to one of political conflict and diverse interpretations. It also illustrates the complex interaction of religious, political, and social factors in shaping the course of Islamic history, making it a crucial moment for understanding the evolution of political thought in Islamic civilization.